Pemberdayaan Masyarakat Melalui Pemerintahan Desa Menuju Kemandirian Sosial: Empowering Communities Through Village Governance Towards Social Independence - Setyobudi, Teguh (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This study aims to explore and analyze the role of community empowerment through village government in achieving social independence. Community empowerment at the village level is a crucial strategy for increasing local capacity and social resilience. Through case studies in several villages, this study identifies various initiatives and programs implemented by village governments, including skills training, economic counseling, and infrastructure development. The results show that the active involvement of village governments in designing and implementing empowerment programs significantly contributes to increasing community social independence. These programs not only improve economic welfare and health but also encourage active community participation in the decision-making process. This study concludes that effective community empowerment through village government can accelerate the achievement of social independence and create more resilient and independent communities.